One Examination about Measuring Gender Empowerment: Through Making New Type of GEM - Tomita, Akiko (International Relations, 2010)
Gender Empowerment measuring is the indicator that measures female participation in political and economic scenes. There are two different ideas about the concept of “gender empowerment (GE)”. One is the idea thought by UNDP (United Nations Development Program). They think that gender empowerment can be accomplished by the movement of individual woman in national, formal level. And they focus on only politics and economics. On the other hand, South women and many feminists claim the importance of national, formal, and transnational, and local, informal level. And, they focus on individual women and women in the group. And, they consider not only political, economical aspects, but also social and culture aspects. As above, there are two different ideas about the concept of “gender empowerment (GE)” internationally. I think that the latter idea suits to modern gender empowerment condition. Gender empowerment in modern times can be seen not only in national, formal level, but also in local, informal levels. And, I focus on political gender empowerment this time. Concretely, I make new type of GEM. That is the indicator that is added the aspect of local, informal, group. By seeing the output of this indicator, I can measure gender empowerment condition in modern times more realistically and adequately. In this thesis, I think that this new GEM can measure gender empowerment more realistic than the present GEM. And, I can suggest another and original thought about gender empowerment condition by seeing the transition between the present GEM and new GEM. This is the point of my thesis.